2019
DOI: 10.1177/1098612x19871701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four inflation techniques on endotracheal tube cuff pressure using a feline airway simulator

Abstract: Objectives The aim of this study was to compare four inflation techniques on endotracheal tube cuff (ETC) pressure using a feline airway simulator. Methods Ten participants used four different endotracheal cuff inflation techniques to inflate the cuff of a low-pressure, high-volume endotracheal tube within a feline airway simulator. The simulator replicated an average-sized feline trachea, intubated with a 4.5 mm endotracheal tube, connected to a circle breathing system and pressure-controlled ventilation with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
3
2
1
Order By: Relevance
“…Our results revealed very limited use of cuff manometers but common use of MOV to establish a cuff seal in dogs, cats and farm animals. This result is not in line with evidence obtained in humans [ 27 , 28 , 29 ], as well as in dogs and cats [ 1 , 2 , 30 , 31 ] establishing the inferiority of MOV to the use of a manometer in achieving a pre-specified (i.e., target) cuff pressure. Furthermore, when comparing MOV in cats and dogs to the use of commercially available syringe inflation devices, MOV proved inferior [ 2 , 32 ].…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Our results revealed very limited use of cuff manometers but common use of MOV to establish a cuff seal in dogs, cats and farm animals. This result is not in line with evidence obtained in humans [ 27 , 28 , 29 ], as well as in dogs and cats [ 1 , 2 , 30 , 31 ] establishing the inferiority of MOV to the use of a manometer in achieving a pre-specified (i.e., target) cuff pressure. Furthermore, when comparing MOV in cats and dogs to the use of commercially available syringe inflation devices, MOV proved inferior [ 2 , 32 ].…”
Section: Discussioncontrasting
confidence: 66%
“…This result is not in line with evidence obtained in humans [ 27 , 28 , 29 ], as well as in dogs and cats [ 1 , 2 , 30 , 31 ] establishing the inferiority of MOV to the use of a manometer in achieving a pre-specified (i.e., target) cuff pressure. Furthermore, when comparing MOV in cats and dogs to the use of commercially available syringe inflation devices, MOV proved inferior [ 2 , 32 ]. Whereas these studies clearly concluded that a cuff manometer should be used to achieve optimal ETT cuff pressure, the use of MOV was three times more common than cuff pressure measurement in dogs and cats in the current study.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…Studier har vist at helsepersonell som bruker palpasjon og minimal-lekkasjemetoden av indikatorballongen i endotrakealtuber hadde problemer med å opprettholde riktige cufftrykk (8,9). Dette inkluderer også helsepersonell med lang erfaring i å håndtere endotrakealtuber (10,11).…”
Section: Bakgrunnunclassified